Association pattern between dimensions of fish and otolith to expedite morphometric variations of three geographically isolated stocks of Tenualosa ilisha (Hamilton, 1822) from diverse ecosystems - Borah, Simanku; Vaisakh, G.; Jaiswar, A. K.; Bhattacharjya, B. K.; Sahoo, A. K.; Deshmukhe, G.; Behera, B. K.; Meena, D. K.; Raman, R. K.; Das, B. K. (Indian Journal of Fisheries, 2019)
An attempt was made to establish association pattern between dimension of fish and otolith to expedite morphometric variations of geographically isolated stocks of Tenualosa ilisha (Hamilton, 1822), from three diverse ecosystems; viz., an estuarine (brackish water), a riverine (freshwater) and a lacustrine (freshwater) ecosystem. Sampling was carried out during the period from September 2017 to February 2019 and a total of 196 otoliths were sampled from Narmada Estuary (n=69), Brahmaputra River (n=75) and Ukai Reservoir (n=52) of India. Mean otolith length recorded was 3.55±0.14 mm, 5.18±0.09 mm and 3.85±0.07 mm for samples collected from Narmada Estuary, Brahmaputra River and Ukai Reservoir respectively. Otolith length-weight relationship (OLWR) from three ecosystems showed negative allometric b values ranging from 1.9046-2.5048, with significant difference between Narmada Estuary and Brahmaputra River (p<0.05). Power regression analysis of otolith dimensions (length and width) to total length of fish (TL) and otolith length (OL) to total weight of fish (TW) showed that data fitted well to the model as evident from R2 values (>0.6); except for relationship between otolith width (OB) and TL in samples from Brahmaputra River (R2=0.459). Present study provides first-hand information on association pattern of dimension of fish body and otolith of T. ilisha which can be used in geographical mapping of stock profile of the species. Keywords: Estuarine, Hilsa, Lacustrine, Otolith, Riverine, Tenualosa ilisha